2008
DOI: 10.1007/bf03395641
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Test of a Cognitive Defusion Exercise: Coping With Negative and Positive Self-Statements

Abstract: This study investigated the impact of defusion on a nonclinical sample ( n = 60)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 18 publications
3
50
0
2
Order By: Relevance
“…It shows that state self-esteem can be influenced by how a person integrates performance feedback (negative or positive). Previous studies mainly focused on the interaction between environmental feedback and individuals' self-concept (e.g., Healy, Barnes-Holmes, Barnes-Holmes, & Keogh, 2008;Merwin & Wilson, 2005), but few studies have paid attention to the effect of inner feedback of individuals' own behaviors on their self-concept. This study showed that individuals could actively adopt some strategies to influence their own self-concept.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…It shows that state self-esteem can be influenced by how a person integrates performance feedback (negative or positive). Previous studies mainly focused on the interaction between environmental feedback and individuals' self-concept (e.g., Healy, Barnes-Holmes, Barnes-Holmes, & Keogh, 2008;Merwin & Wilson, 2005), but few studies have paid attention to the effect of inner feedback of individuals' own behaviors on their self-concept. This study showed that individuals could actively adopt some strategies to influence their own self-concept.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…Several focused studies have investigated the effects of specific cognitive defusion techniques on negative self-referential thoughts (e.g., Healy et al, 2008;Masuda, Hayes, Sackett, & Twohig, 2004;Masuda et al, 2009). One study investigated the effects of a commonly used cognitive defusion technique, "I am having a thought that…" (Healy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One study investigated the effects of a commonly used cognitive defusion technique, "I am having a thought that…" (Healy et al, 2008). The study suggests that negative self-referential statements (e.g., "my life is pointless") when presented in the defused format (e.g., "I am having a thought that my life is pointless") can decrease the emotional discomfort associated with that statement and increase willingness to be exposed to these statements.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian lain menyimpulkan bahwa strategi cognitive defusion dapat digunakan untuk mengurangi pernyataan diri negatif (Healy et al, 2008). Subjek dalam penelitian ditugaskan sebagai salah satu dari tiga kondisi eksperimen, yaitu pro-defusion, anti-defusion, dan netral.…”
Section: Pembahasanunclassified